The Needs Analysis of Teaching Materials for Writing Short Stories Based on Cerpengram Method for Class IX - Dita Rosa Utami; Zainal Rafli; Siti Ansoriyah (LAFADZ JAYA Publisher, 2023)
The advancement of science impacts learning innovations that fulfill the requirements for resolving issues in the field of education. The goal of this project is to find instructional resources for writing short stories that are appropriate for class IX students. This research used a descriptive qualitative methodology to collect data using interviews and questionnaires. The findings indicated that there were constraints and a lack of teaching resources for class IX students at SMP Negeri 24 Kerinci to write short stories. The final results indicate that creative teaching tools based on the Cerpengram technique are required to facilitate comprehension of the subject matter, particularly short story writing abilities. According to the requirements analysis, 100% of students and instructors demand novel teaching resources based on the Cerpengram technique that have been produced in the form of e-modules.